The Cytoreductive Effect of Radiotherapy for Small Cell Ovarian Carcinoma of the Pulmonary Type: A Case Report and Review of the Literature - Shuhei Terada; Takashi Suzuki; Akihiro Hasegawa; Satoru Nakayama; Hiroshi Adachi (Hindawi Limited, 2018)
Small cell ovarian carcinoma of the pulmonary type is a rare and highly aggressive tumor for which a suitable treatment strategy has not been established. A 45-year-old woman presented with abdominal swelling, and primary ovarian carcinoma was suspected. The postoperative pathological diagnosis was small cell ovarian carcinoma of the pulmonary type. She also had complicated grade 1 endometrioid carcinoma of the uterine corpus. Three courses of cisplatin and etoposide therapy were administered as adjuvant chemotherapy. Because the tumor was chemotherapy resistant, she underwent palliative abdominal irradiation at a dose of 26 Gy in 13 fractions, which induced cytoreduction and provided symptomatic relief. She died 4 months after surgery. Lactate dehydrogenase was a useful tumor marker during treatment. Here, we present an extremely rare case of a patient with small cell ovarian carcinoma of the pulmonary type treated with radiotherapy after surgery and chemotherapy.